2017
DOI: 10.1111/jcpt.12607
|View full text |Cite
|
Sign up to set email alerts
|

Transporter genesABCG2rs2231142 andABCB1rs1128503 polymorphisms and atorvastatin response in Chilean subjects

Abstract: SummaryWhat is known and objective: Statins are first-line therapy for reducing high cholesterol levels. However, response to these drugs shows high interindividual variability.We aimed to investigate the influence of two single nucleotide polymorphisms (SNP) (ABCB1 rs1128503 and ABCG2 rs2231142) in the ABC transporter genes on response to short-term low-dose atorvastatin in Chilean hypercholesterolaemic patients. Methods:We studied 127 Chilean hypercholesterolaemic patients treated with 10 mg/d atorvastatin f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This variation has been associated with polymorphisms in genes encoding drug metabolizing enzymes and transporters (34). However, differences in allele frequencies and their effect on quantitative parameters including cholesterol levels, arterial pressure and pharmacokinetic parameters, and associations of genotypes with drug metabolism and response have been documented across various populations (7,33,35,36).…”
Section: Discussionmentioning
confidence: 99%
“…This variation has been associated with polymorphisms in genes encoding drug metabolizing enzymes and transporters (34). However, differences in allele frequencies and their effect on quantitative parameters including cholesterol levels, arterial pressure and pharmacokinetic parameters, and associations of genotypes with drug metabolism and response have been documented across various populations (7,33,35,36).…”
Section: Discussionmentioning
confidence: 99%
“…An ATS intrinsic uptake clearance of 2030 mL/min (95% CI: 1140–2620 mL/min) was predicted and, assuming the same passive diffusion across the cell membrane of hepatocytes and HEK293 cells (120 µL/min/g of liver), transporter-mediated active uptake of ATS dominates overall ATS hepatic uptake [ 34 ]. Moreover, polymorphisms in transporter genes have been reported to affect the PK of statins and their therapeutic effects [ 35 , 36 ]. It has been demonstrated that the liver-to-plasma concentration ratio of ATS is 2.7-fold higher ( p = 0.002) in wild-type when compared to Slco1b2− / − mice after 1 mg/kg ATS tail vein injection [ 33 ].…”
Section: Distributionmentioning
confidence: 99%
“…Atorvastatin is a substrate for the efflux transporters P-glycoprotein, encoded by ABCB1, and BCRP, encoded by ABCG2, which may limit intestinal absorption and biliary clearance of AT. The common SNPs of ABCB1 (rs1045642, rs1128503 and rs2032582) have been reported to be associated with the lipid-lowering efficacy of atorvastatin (Thompson et al, 2005;Hoenig et al, 2011;Prado et al, 2018), but their association with plasma AT concentration is unknown. The ABCG2 (421C>A) variant (rs2231142) contains a replacement of glutamine with lysine at position 141 in the intracellular region of the protein, and demonstrates lower protein expression and transport capacity in cells transfected with the variant than with the wild type (Imai et al, 2002;Kondo et al, 2004).…”
Section: Introductionmentioning
confidence: 99%